The Relationship between Work Motivation and Workload on Employee Job Satisfaction at PT. Pratomo Putra Teknik Palopo - Rima Rima; Indra Kusdarianto; Samsinar (Jurnal Economic Resource, 2023)
This study aims to determine the relationship between work motivation and workload on employee satisfaction at PT Pratomo Putra Teknik Palopo. The research method used was quantitative research with a total of 40 respondents. Data collection techniques were carried out by distributing questionnaires directly to employees at PT Pratomo Putra Palopo. The results of this study indicate that work motivation has a significant effect on job satisfaction, while workload has a positive effect on employee satisfaction, while workload has a positive effect on employee satisfaction because the influence of employee satisfaction has increased by 0.400 units. The regression coefficient of the work motivation variable has a positive relationship with employee satisfaction.